Upaya Peningkatan Kemampuan Membaca Melalui Buku Cerita Bergambar Pada Anak Usia Dini - Nikmah, Novalia Ungzilatun; Darwati, Yuli (Institut Agama Islam Negeri Ponorogo, 2021)
Early reading is a unique and important skill for children’s language development, as well as a means of communication for humans. Individuals will acquire new information, knowledge and new experiences through reading. The main and fundamental problem in this study is that many children are not able to read fluently. This study is aimed at early childhood with reading delays. This study aims to determine the improvement of reading comprehension through the method of reading picture story books. The method used in this research is descriptive and qualitative methods, the data is collected through observation and documentation. Based on the results of study, it was found that there was an increase in reading comprehension with picture story books.